FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN TUBERCULOSIS DI KECAMATAN KALIANGKRIK MAGELANG (Studi tentang Kontak Langsung dengan Pasien BTA Positif Tuberculosis) - Tuti Susilowati (Jurnal Komunikasi Kesehatan, 2011)
In Indonesia, Tuberculosis is the main problem of health in society, which caused bybacillus of Mycobacterium tuberculosis. Indonesia was big three contributor of tuberculosispatient in word after China and India. Patient of BTA Positif tuberculosis of lung was asource of infection to its environment, particularly which live in house. This research aimedto know some factors related to occurrence of tuberculosis of lung in Sub-district ofKalinagkrik Regency of Magelang at house which there are patient of BTA positivetuberculosis of lung.This research using survey method, and cross sectional approach. Its population is allpatient of BTA positif tuberculosis of which noted since January 2007 to Desember 2010along with familys members which complying inclution criteria. Observation for adulttuberculosis suspect done by observation of SPS sputum, while for children by Roentgen.Result of research indicates that variable of contact periode, density of house dwelling andcloseness of status in family statistically not correlate to occurrence of tuberculosis ofVariable of history of sleep together in room (ρ value = 0,020), and sputum isolation in ahouse contact ( ρ value < 0,001) correlating to occurrence of tuberculosis of lung. From 102responders of in a house contact of family member resulted that 12 patients of new lungtuberculosis with detail that is 6 is BTA positif tuberculosis of lung, 3 is BTA negative,positif RO and 3 is Tuberculosis of child. Preventative effort of tuberculosis infection cane bemade by taking care of the body condition keep healthy, improving goodly sputum isolation,heightening nutrition intake, minimizing to contact with patient in order that occurrence canbe avoided.